POLE and POLD1 pathogenic variants in the proofreading domain in papillary thyroid cancer - Abdul K Siraj (Endocrine Connections, 2020)
Thyroid cancer is the most frequent endocrine cancer with an increasing incidence rate worldwide and is the second most common malignancy among females in Saudi Arabia. Papillary thyroid cancer (PTC) is the most common subtype. Germline pathogenic variants in the proofreading domain of the POLE and POLD1 genes predispose to several types of cancers. However, the role of pathogenic variants of these two genes in PTC remains unknown. Capture sequencing, Sanger sequencing and immunohistochemistry were performed on 300 PTC cases from the Middle Eastern region. One germline pathogenic variant each of POLE (1/300, 0.33%) and POLD1 (1/300, 0.33%) genes was identified. Low expression of POLD1 was detected in 46.5% (133/286) of cases an d was significantly associated with the follicular variant of PTC (P = 0.0006), distant metastasis (P = 0.0033) and stage IV tumours (P = 0.0081). However, no somatic pathogenic variant was detected in POLE gene. Furthermore, low expression of POLE was noted in 61.7% (175/284) of cases with no significant clinicopathological associations. Our study shows that pathogenic variant in the POLE and POLD1 proofreading domain is a cause of PTC and low expression of POLD1 is associated with poor prognostic markers in the Middle Eastern population. Further studies from different geographic populations are needed to determine the frequency and spectrum of proofreading domain pathogenic variants in POLE and POLD1 genes and in PTC from different ethnicities.